PENGARUH PENGGUNAAN MEDIA GARIS BILANGAN PADA MATERI PENJUMLAHAN DAN PENGURANGAN BILANGAN BULAT TERHADAP HASIL BELAJAR SISWA KELAS V DI SD NEGERI 17 BANING SUNGAI ANA SINTANG TAHUN 2023/2024 - Wibowo, Dwi Cahyadi; Cen, Sovia; Rusdi, Rusdi; Putri, Anike (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to investigate the effect of using number line media on students’ learning outcomes in addition and subtraction of integers for fifth-grade students at SD Negeri 17 Baning Sungai Ana Sintang. This research employed a quantitative quasi-experimental design, and data were analyzed using SPSS Statistic 25.0. The results of the Paired Sample T-Test showed a significance value (2-tailed) of 0.000 ? 0.05, indicating a significant difference between pretest and posttest scores in the experimental class, which increased from 49 to 89. The comparison between the experimental and control classes revealed a t-value of 5.218 > t-table 1.688, confirming that the experimental class achieved better learning outcomes. Teacher response questionnaires showed a percentage of 82%, and student response questionnaires showed 92%, indicating very strong approval. It is concluded that the use of number line media effectively improves students’ understanding and performance in integer operations. Future researchers are suggested to select materials that align with the use of number line media to further enhance the quality and effectiveness of the study.